Factors Influencing Depression and Anxiety among Black Sexual Minority Men. (18th September 2011) - Graham, Louis F.; Aronson, Robert E.; Nichols, Tracy; Stephens, Charles F.; Rhodes, Scott D.
Abstract : The primary aim of this study was to examine the relationships between depression and anxiety, and ethnic and sexual identity development, and discrimination and harassment (DH) among Black sexual minority men. Additional aims were to determine whether an interaction effect existed between ethnic and sexual identity and whether coping skills level moderated these relationships. Using an observational cross-sectional design, 54 participants recruited through snowball sampling completed self-administered online surveys. Stepwise multiple regression analysis was used. Sixty-four percent of the variance in depression scores and 53% of the variance in anxiety scores were explained by DH and internalized homonegativity together. Thirty percent of the sample had scale scores indicating likelihood of depression and anxiety. Experience of DH and internalized homonegativity explained a large portion of the variability in depression and anxiety among Black sexual minority men. The study showed high prevalence of mental distress among this sample.